2022
DOI: 10.1371/journal.pone.0264759
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic effects of probiotics or synbiotics on postoperative ileus after gastrointestinal cancer surgery: A meta-analysis of randomized controlled trials

Abstract: Background Postoperative ileus is a major problem following gastrointestinal cancers surgery, several randomized controlled trials have been conducted investigating the use of probiotics or synbiotics to reduce postoperative ileus, but their findings are controversial. Objective We conducted a meta-analysis to determine the effect of probiotics or synbiotics on early postoperative recovery of gastrointestinal function in patients with gastrointestinal cancer. Methods The Embase, Cochrane Library, PubMed, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…Gastrointestinal motility, as the core part of the accelerated recovery of patients undergoing gastrointestinal surgery, has important clinical significance and has received close attention from surgeons [ 35 ]. A delayed recovery of gastrointestinal function after surgery, namely, postoperative ileus, with the clinical manifestations of abdominal distension and pain, sometimes delayed gastric emptying and vomiting, and gastrointestinal dysmotility with delayed passing of first flatus and defecation, eventually leading to the prolongation of hospital stay and even increased morbidity [ 36 , 37 ].…”
Section: To Enhance Gut Motilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Gastrointestinal motility, as the core part of the accelerated recovery of patients undergoing gastrointestinal surgery, has important clinical significance and has received close attention from surgeons [ 35 ]. A delayed recovery of gastrointestinal function after surgery, namely, postoperative ileus, with the clinical manifestations of abdominal distension and pain, sometimes delayed gastric emptying and vomiting, and gastrointestinal dysmotility with delayed passing of first flatus and defecation, eventually leading to the prolongation of hospital stay and even increased morbidity [ 36 , 37 ].…”
Section: To Enhance Gut Motilitymentioning
confidence: 99%
“…Then, the inflammatory phase follows, with the release of a large number of inflammatory mediators, such as interleukin-6, interleukin-1, monocyte chemoattractant protein-1 and cell adhesion molecule-1, which damage intestinal muscles and further inhibit the recovery of gastrointestinal function. Last, but not least, anesthesia and the pharmacological interventions thereafter, mainly opioids often used as analgesics, have a major impact by means of activation of μ-opioid receptors, which in turn inhibit acetylcholine release from myenteric fibers [ 35 , 38 , 39 ].…”
Section: To Enhance Gut Motilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Meta‐analyses and systematic reviews have revealed that gut dysbiosis is closely related to human health, chemotherapy‐related side effects, and surgery‐related complications and diseases 12–14 . In this study, we investigated the effects of systemic chemotherapy with GC on the gut microbiome.…”
Section: Introductionmentioning
confidence: 99%
“…Meta‐analyses and systematic reviews have revealed that gut dysbiosis is closely related to human health, chemotherapy‐related side effects, and surgery‐related complications and diseases. 12 , 13 , 14 In this study, we investigated the effects of systemic chemotherapy with GC on the gut microbiome. We hypothesized a potential link between chemotherapy‐induced gut dysbiosis and decreased anti‐tumor immunity, driving us to explore novel interventions for targeted microbiome modulation by supplementing with probiotics, prebiotics, and synbiotics to retain anti‐tumor immunity.…”
Section: Introductionmentioning
confidence: 99%